Предмет: Алгебра,
автор: zombie14
Решите карточку по алгебре,состоящую из 4 заданий
Приложения:
![](https://files.topotvet.com/i/56b/56bb61378b3f1178efc7bbd29725f4ce.jpg)
Ответы
Автор ответа:
1
1) с(3х+5у)- у (5с- 2х)= =3сх+5ус-5ус+2ху=
=3сх+2ху
2)
![\frac{15 b}{5 - b} -3 b = \frac{15b - 15b + 3 {b}^{2} }{5 - b} = \frac{3 {b}^{2} }{5 - b} \frac{15 b}{5 - b} -3 b = \frac{15b - 15b + 3 {b}^{2} }{5 - b} = \frac{3 {b}^{2} }{5 - b}](https://tex.z-dn.net/?f=+%5Cfrac%7B15+b%7D%7B5+-+b%7D+-3+b+%3D+%5Cfrac%7B15b+-+15b+%2B+3+%7Bb%7D%5E%7B2%7D+%7D%7B5+-+b%7D+%3D+%5Cfrac%7B3+%7Bb%7D%5E%7B2%7D+%7D%7B5+-+b%7D+)
3) 4х-4х²=1
4х²-4х+1=0
(2х-1)²=0
2х-1=0
х=½
4)
![\frac{4}{ {x}^{2} - 9 } - \frac{2}{ {x}^{2} + 3x } = \\ = \frac{4}{(x - 3)(x + 3)} - \frac{2}{x(x + 3)} = \\ = \frac{4x - 2(x - 3)}{x(x - 3)(x + 3)} = \frac{2x + 6}{x(x - 3)(x + 3)} = \\ = \frac{2(x + 3)}{x(x - 3)(x + 3)} = \frac{2}{x(x - 3)} \frac{4}{ {x}^{2} - 9 } - \frac{2}{ {x}^{2} + 3x } = \\ = \frac{4}{(x - 3)(x + 3)} - \frac{2}{x(x + 3)} = \\ = \frac{4x - 2(x - 3)}{x(x - 3)(x + 3)} = \frac{2x + 6}{x(x - 3)(x + 3)} = \\ = \frac{2(x + 3)}{x(x - 3)(x + 3)} = \frac{2}{x(x - 3)}](https://tex.z-dn.net/?f=+%5Cfrac%7B4%7D%7B+%7Bx%7D%5E%7B2%7D+-+9+%7D+-+%5Cfrac%7B2%7D%7B+%7Bx%7D%5E%7B2%7D+%2B+3x+%7D+%3D+%5C%5C+%3D+%5Cfrac%7B4%7D%7B%28x+-+3%29%28x+%2B+3%29%7D+-+%5Cfrac%7B2%7D%7Bx%28x+%2B+3%29%7D+%3D+%5C%5C+%3D+%5Cfrac%7B4x+-+2%28x+-+3%29%7D%7Bx%28x+-+3%29%28x+%2B+3%29%7D+%3D+%5Cfrac%7B2x+%2B+6%7D%7Bx%28x+-+3%29%28x+%2B+3%29%7D+%3D+%5C%5C+%3D+%5Cfrac%7B2%28x+%2B+3%29%7D%7Bx%28x+-+3%29%28x+%2B+3%29%7D+%3D+%5Cfrac%7B2%7D%7Bx%28x+-+3%29%7D+)
(при х≠±3, х≠0)
=3сх+2ху
2)
3) 4х-4х²=1
4х²-4х+1=0
(2х-1)²=0
2х-1=0
х=½
4)
(при х≠±3, х≠0)
zombie14:
Спасибо!
Похожие вопросы
Предмет: Физика,
автор: sofitkachetserp
Предмет: Геометрия,
автор: katyasha558
Предмет: Музыка,
автор: lovelove1564
Предмет: Математика,
автор: ZombieMainer
Предмет: Математика,
автор: galinamukina197